Dielectric Spectroscopy of Composites of Epoxy Resin - Fareeda Farrukh ,; Shahid H. Zaidi, (Journal of Basic & Applied Sciences, 2021)
The dielectric behavior of composite of epoxies having different composition of prepolymer and epoxy equivalent is investigated in the frequency range 1E-1Hz to 1E5Hz at room temperature. The measurements presented consist of two sets of sample of epoxy resin with two different proportions 1:1 and 1:0.5 of resin and hardener. Samples having different proportion of resin and hardener shows low frequency dispersion (LFD) in the frequency range below 3 KHz at small thickness (less than 0.38mm). At large thickness the sample response is similar for the two different proportions.